Isolamento e caracterização molecular de Anaplasma marginale de origem congênita e avaliação da virulência em bezerros experimentalmente infectados - Rodrigo Melo Meneses (2013)
Difference in virulence among isolates of Anaplasma marginale in calves with vertical infection has been observed. Thus, this study aimed to identify the vertical infection of A. marginale in newborn calves, molecularly characterize the samples and testing the virulence of one of the isolates. Blood samples were colected of 30 newborn Holstein calves to identification of A. marginale by PCR. The positive animals had samples sequenced and characterized. Eight calves free of hemoparasitic infection were inoculated with one of the isolates (UFMG3) and rickettsemia, packed cell volume (PCV) and clinical parameters were evaluated. Among the 30 calves accompained, three (10%) were positive for A. marginale, with three different nucleotide sequences of high similarity (97-99%) with strains deposited in Genbank. UFMG3 was highly similar to the isolate I19-brown brocket deer (Mazama gouazoubira). Incubation, patent and convalescent periods were 20, nine and 31 days, respectively. The rickettsemia reached maximum values of 3.78 and 5.1%. The lowest value of PCV was 13.5% one day after the rickettsemia peak. Hyperpyrexia, tachycardia, tachypnea and reduced ruminal movements were seen together at the anemia peak as well as other clinical abnormalies were evident around this period. It is concluded, therefore, that vertical transmission of A. marginale occurs frequently and different isolates are capeble of being vertically transmited in cattle, in addition, UFMG3 has low virulence, could be used as a live vaccine.